Instrument Teacher's Narrative Identity and Professional Growth. (5th February 2016) - Pisto, Tuulia; Jääskeläinen, Visa; Ruokonen, Inkeri; Ruismäki, Heikki
Abstract: The purpose of the study was to discover the dynamics of a music educator's identity formation and the preconditions of professional growth in her life. The music educator's profession was described through her stories and beliefs. First, the research task was to determine when and why individual/social sources of self were successful (dominant) at particular times in her life. Second, the task was to determine when and why certain changes in her life occurred. The instrument teacher had worked at different music institutes and had recently retired. The data has been collected through an episodic, in depth-interview. The data consists of meaningful episodes in the teacher's life and her beliefs on different themes in this study. The data analysis strategies included paradigmatic analysis of narratives and narrative analysis. According to the results, the success of instrument teacher's sources of individual/social selves was defined by her efforts to achieve harmony. Aspirations to achieve integrity arise from the need to define oneself. Thus, answering the question who a person is requires individual/social definitions. According to this study, progression in her professional growth is a maturing process. First, it involved getting to know herself, second, committing to herself and finally achieving autonomy. The instrument teacher's profession is characterized by a relationship between personas. According to her story, instrument teaching is a lifelong preoccupation.